Effects of feeding human-inedible feedstuffs to lactating cows to improve nutriet conversion efficiency - Davidson, Melissa J.; Bennett, Amanda; Takiya, Caio; Ylioja, Caroline; Bradford, Barry J. (My University, 2017)
Dairy cattle, being ruminants, can utilize feeds that are of little nutritional value for humans and other monogastrics. Cattle can convert these ingredients into a valuable human-edible product: milk. Inclusion of such feed ingredients in dairy rations can improve the human-edible production efficiency of milk, defined as human-edible product divided by human-edible inputs. The objective of this study was to evaluate a diet composed only of feedstuffs that are inedible or mostly inedible to humans, with the goal of improving nutrient conversion efficiency. Twelve multiparous Holstein cows (231±40 days in milk and 34.4±7.2 kg/d of milk yield at the start of experiment), were studied in a 3×3 Latin square and received the following treatments: 1) Normal total mixed ration (TMR) for a lactating cow (CON); 2) TMR composed of human inedible feedstuffs (HIF); and 3) HIF with top-dressed rumen-protected amino acids [77 g/d Aji-pro-L (Ajinomoto, Chicago, IL) and 45 g/d MetaSmart (Addiseo, Antony, France); HIF-AA]. The HIF diets consisted of hay (triticale and red clover), corn hominy, corn gluten feed, wheat middlings, spent coffee grounds, whole cottonseed with lint, molasses, and a vitamin/mineral mixture. The study includes three periods lasting 21 days each; feed intake and milk yield were recorded and milk samples were collected over the last 4 days of each period. Cows were housed in tie-stalls and milked twice daily. Preliminary results from period one showed a decrease in milk yield for both the HIF diets [36.2 kg/d (CON) vs. 24.3 kg/d (HIF) and 25.8 kg/d (HIF-AA); P <0.001]. Conversion efficiency of both energy and protein were not improved with either of the HIF diets, likely because of the substantial drop in milk yield. Although avoiding human-edible feedstuffs can in some cases improve human-edible production efficiency, this is not the case when the resulting diet dramatically reduces milk yield.
Keywords: Spring 2017